Functionalization of polyolefins - Chung, T. C. (Academic Press, 2002)
Summarizes the significant experimental results on the functionalization of polyolefins and classifies them into several chemical methods. This book also provides information on the functional polyolefin materials. It covers: chemical approaches in the functionalization of polyolefins, and polyolefin materials and their potential applications.